Realidad local de los grupos de atención prioritaria durante el último trienio en la zona urbana y andina del cantón Santa Ana de Cotacachi. - Galindo Andrade, Juan Manuel (2024)
Priority attention groups in Ecuador have suffered from a permanent violation of their rights, due to social, economic, political, cultural, ideological, geographic, among other factors, which contradicts express provisions established by the Constitution of the Republic of Ecuador (2008). In this sense, the objective of the research was focused on analyzing the local reality of these groups during the last three years in the urban and Andean area of the Cotacachi canton, identifying situations of vulnerability, to structure a draft resolution addressed to the Municipal Decentralized Autonomous Government (GAD), strengthening participation and dialogue mechanisms for comprehensive development and good living, in favor of citizen rights. It was developed methodologically under a socio-critical paradigm, which made it possible to issue a propositional judgment and criterion, recognizing the needs of this population. The approach used was of a mixed nature, that is, qualitative-quantitative, identifying situations of vulnerability and risk factors. Likewise, field research was used, at an exploratory level, using theoretical level methods such as historical-logical, analytical-synthetic and inductive-deductive, and empirical level methods such as the questionnaire and the interview guide to a specific sample chosen intentionally. Based on the obtained results, it is evident that the most affected rights are health, education and work, for this reason it is important to promote participatory spaces and implement strategies for the protection of rights.